Establishing an Audit-Based Bookkeeping System for Msmes: A Strategic Move Toward Business Sustainability - Bangun Kristianto, Giovanny; Dianningsih; Istiningrum, Farida (Majalah Ilmiah UPI YPTK, 2025)
MSMEs represent a strategic sector in the national economy, contributing approximately 60% to the GDP and absorbing more than 97% of the workforce. However, most MSMEs face serious challenges in financial management, such as the absence of a structured bookkeeping system, low accounting literacy, and minimal internal control. This community service initiative aims to enhance the understanding, skills, and practices of audit-based bookkeeping among MSMEs affiliated with ASPIKMAS in Banyumas Regency. The implementation methods include outreach, training, mentoring, and participatory evaluation, involving lecturers and students as facilitators. The results show that MSME partners participated enthusiastically in the program, with the main challenges identified as limited access to capital, weak financial record-keeping, and suboptimal digital marketing strategies. The implementation of automated Excel templates, mobile-based financial recording applications, and education on basic internal auditing emerged as practical solutions tailored to the partners’ needs. This program contributes to improving financial literacy, strengthening competitiveness, and promoting more transparent and sustainable business practices.